The Revival of the "Mothers of the Nation" from the Period of Anti Colonial Movement until the Independence of Indonesia - Ningrum, Siti Utami Dewi (Jurnal Perempuan, 2018)
"Mothers of the Nation" or ibuism is a term that is often considered negative in the study of women's history. This is related to the nation's political journey, during which the New Order regime took power, the terminology was used to control and dominate women in Indonesia. Further explored, in the 1920s, the spirit of nationalism are grew, including among the (priayi) noble women. They formed an association and held the Indonesian Women's Congress I in 1928. According to Susan Blackburn, what women did at the time was their nationalistic form, becoming "Mothers of the Nation." Using a historical approach, this paper seeks to retrace how early noble women came into existence and formulated their ideas of nationalism. The sources used are the result of literature studies, whether magazines, books, scientific papers, memoirs or biographies of women movement. This paper also use oral and photo sources to complete the experiences of women who involved in this topic.